Autorzy:Praca zbiorowa
Wydawnictwo:WSiP
Rok wydania:2013
Zredukuj wyrazy podobne 4.63 gwiazdek na podstawie 8 opinii

`a)\ ul(6xy)+ul(ul(2x^2))-ul(8xy)-ul(ul(3x^2))=` `-2xy-x^2` 

`b)\ ul(3/5a^2)+ul(ul1)-ul(0,2a^2)+ul(ul(ul(3b^2)))-ul(ul3)+ul(ul(ul(1/3b^2)))=` `2/5a^2-2+3 1/3b^2` 

`c)\ sqrt5x+3sqrt5x=4sqrt5x` 

`d)\ ul(2sqrt6x)-ul(ul(5sqrt3y))-ul(sqrt6x)+ul(ul(4sqrt3y))=` `sqrt6x-sqrt3y` 

`e)\ (4x-y)-(3x+2y)=` `4x-y-3x-2y=` `x-3y` 

`f)\ -(-a-5)-(-2-3a)-2a-1=`  

`\ \ \ =a+5+2+3a-2a-1=` `2a+6`